2021
DOI: 10.3390/ijms22020544
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of MKK and MAPK Gene Families in Brassica Species and Response to Stress in Brassica napus

Abstract: Mitogen-activated protein kinase (MAPK) cascades are common and conserved signal transduction pathways and play important roles in various biotic and abiotic stress responses and growth and developmental processes in plants. With the advancement of sequencing technology, more systematic genetic information is being explored. The work presented here focuses on two protein families in Brassica species: MAPK kinases (MKKs) and their phosphorylation substrates MAPKs. Forty-seven MKKs and ninety-two MAPKs were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 90 publications
3
13
0
Order By: Relevance
“…To date, an increasing number of studies have shown that members of the ABC transporters family can play an important role in response to different stresses (Wang et al, 2021). In potato we observed upregulation of Stabct3 and Stabct51 under heat stress and similar results also seen in rice (Moon and Jung, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…To date, an increasing number of studies have shown that members of the ABC transporters family can play an important role in response to different stresses (Wang et al, 2021). In potato we observed upregulation of Stabct3 and Stabct51 under heat stress and similar results also seen in rice (Moon and Jung, 2014).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, Ca 2+ /CaM-dependent proteins have been reported in various plants including: Vitis vinifera [105], Zea mays L [106], soybean [107], Brassica napus [108], Populus trichocarpa [109], citrus trees [110], and other Gossypium species [111]. Kinases and their profile expressions under cold stress have been recently reported in Brassica napus [112], Jatropha curcas [113], and Common vetch [114]. The Mitogen-Activated Protein Kinase (MAPK) cascade regulates cold stress through the binding roles of Calcium/Calmodulin-Regulated Receptors Kinase-Like 1 (CRKL1) [115].…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascade and Hormonal...mentioning
confidence: 99%
“…In Arabidopsis, phosphorylated MPK6 mediates the negative expression of CBF3 by activating a negative regulator, MYB15 [122]. On the contrary, MPK4/6 activates CBF expression by inhibiting the MKK4/5-MPK3/6 pathway [112] Figure 4. The ICE-CBF-COR response pathway to cold stress initiates at the plasma membrane to plant cold tolerance.…”
Section: Mitogen-activated Protein Kinase (Mapk) Cascade and Hormonal...mentioning
confidence: 99%
“…This suggests that potato MAPK genes have a substantial role in plant growth, development, and response to various stresses. To date, an increasing number of studies have shown that members of the MAPK family can play an important role in response to different stresses [ 53 ]. In potato, StMAPK2 , StMAPK6 , and StMAPK19 are upregulated in response to heat stress.…”
Section: Discussionmentioning
confidence: 99%